The clinical role of daily blood pressure monitoring for the management of patients at the ambulatory stage - O. S. Kulbachuk; Ye. V. Sid; O. V. Soloviov; A. V. Piskun (Сучасні медичні технології)
The aim of the work is to analyze and evaluate the clinical role of daily blood pressure monitoring for the management of patients with arterial hypertension.